2007
DOI: 10.1159/000102591
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Abdominal Adhesions – Present State and What’s beyond the Horizon?

Abstract: Intra-abdominal adhesions are normally found after most surgical procedures. Many of the adhesions are asymptomatic, but in about 5% they will lead to readmission due to adhesion-related disorders, such as small bowel obstruction, pelvic pain and infertility. This review discusses possible ways to prevent abdominal adhesions and provides an update as comes to where we stand today in research regarding experimental and clinical use of various antiadhesive agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 156 publications
0
30
0
8
Order By: Relevance
“…Research to date has identified four main aspects of methods to prevent the formation of intestinal adhesions after abdominal surgery: 1) use of minimally invasive surgical procedures, such as laparoscopic surgery to reduce peritoneal trauma; 2) prevention of fibrin formation with pharmacological agents, such as heparin or tissue plasminogen activator; 3) reduction of the contact between organs and intra-abdominal contents by using biodegradable barriers such as Seprafilm; and 4) a wide range of biologically active substances in the form of simple fluids, gels, and solids, either combined or alone, have been investigated both clinically and experimentally to reduce or prevent abdominal adhesions (Tingstedt et al, 2007;Lauder et al, 2010;Takagi et al, 2013;Ten Broek et al, 2013a,b). An ideal barrier should be biodegradable, biocompatible, and surgically easy to handle and should act locally to avoid side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Research to date has identified four main aspects of methods to prevent the formation of intestinal adhesions after abdominal surgery: 1) use of minimally invasive surgical procedures, such as laparoscopic surgery to reduce peritoneal trauma; 2) prevention of fibrin formation with pharmacological agents, such as heparin or tissue plasminogen activator; 3) reduction of the contact between organs and intra-abdominal contents by using biodegradable barriers such as Seprafilm; and 4) a wide range of biologically active substances in the form of simple fluids, gels, and solids, either combined or alone, have been investigated both clinically and experimentally to reduce or prevent abdominal adhesions (Tingstedt et al, 2007;Lauder et al, 2010;Takagi et al, 2013;Ten Broek et al, 2013a,b). An ideal barrier should be biodegradable, biocompatible, and surgically easy to handle and should act locally to avoid side effects.…”
Section: Discussionmentioning
confidence: 99%
“…В этом вопросе пока единствен-ным общепринятым выходом остается применение противоспаечных средств [1,2]. Были предложены противоспаечные барьерные средства для местного применения и препараты общего воздействия, од-нако немногие из них нашли клиническое примене- …”
Section: актуальность проблемыunclassified
“…Лапаротомия приводит к образованию спаек в 95-100% случаев и спаечной тонкокишеч-ной непроходимости (СТКН) в 3% случаев [1,2]. Mорфологически невыраженные и клинически асимптоматичные спайки обычно не представля-ют угрозы, но в 5% случаев после внутрибрюшных операций спайки приводят к повторной госпитали-зиции по поводу кишечной непроходимости, абдо-минальных и тазовых болей, бесплодия у женщин [2]. Каждое лапаротомическое вмешательство по поводу кишечной непроходимости приводит к об-разованию новых, более распространенных спаек, что повышает риск возникновения непроходимо-сти.…”
Section: актуальность проблемыunclassified
“…During the last decades, a number of film barriers such as Interceed (oxidized regenerated cellulose), PRECLUDE Peritoneal Membrane (expanded polytetra-fluoroethylene), SurgiWrap (polylactic acid film), and Seprafilm (sodium hyaluronate and carboxymethylcellulose membrane) have become commercially available [7]. However, most of them were tried in abdominal cavities and the results were not as positive as expected [8,9]. In addition, the technical obstacles associated with film barriers may limit their use in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%